Myrtus communis leaf extract protects against cerulein-induced acute pancreatitis in rats - ŞEN, ALİ; ERTAŞ, BÜŞRA; ÖZBEYLİ, DİLEK; ŞENER, GÖKSEL; ÖZKAN YENAL, NAZİYE; KAYA, ÖZLEM TUĞÇE; AYDEMİR, SEZGİN (WILEY, 2020)
In this study, the aim was to examine the potential protective effects of Myrtus communis subsp. communis leaf ethanol extract (MC) treatment against acute pancreatitis (AP) in rats. Thirty-two rats were grouped as the saline-pretreated control (C), MC-pretreated control (MC), saline-pretreated AP (AP), and MC-pretreated AP (MC + AP) groups. To induce AP, cerulein was administered (50 mu g/kg) two times. The rats were given MC for 14 days before cerulein injection. Six hours after the final cerulein injection, the rats were sacrificed. Pancreatic damage was associated with an increase in the serum activity of lipase and amylase, the pancreatic activity of myeloperoxidase, and the pancreatic level of malondialdehyde, interleukin-1 beta, and interleukin-6. AP also led to a decrease in the pancreatic level of anti-inflammatory interleukin-10 and glutathione. Pretreatment with MC before the induction of AP significantly reduced the pancreatic damage observed during the histological examination as well as reversed the biochemical changes evoked by AP. Practical applications Acute pancreatitis is characterized by high mortality (average about 5%; severe cases may reach about 30%). The current treatment for acute pancreatitis is mainly symptomatic. The introduction of herbal drugs may lead to the development of a new strategy in the treatment of this disease. This study revealed that MC reduced pancreatic injury by decreasing pro-inflammatory cytokines, increasing antioxidant capacity and anti-inflammatory cytokine, IL-10. To the authors' knowledge, this research is the first report showing that MC inhibits the development of AP. This observation suggests that MC may be useful in the prevention and the treatment of AP in clinical settings.
Keywords: acute pancreatitis; anti-inflammatory effect; antioxidant effect; IL-10; Myrtus communis subsp; communis leaf ethanol extract; OXIDATIVE STRESS; REACTIVE OXYGEN; ANTIOXIDANT; INFLAMMATION; DYSFUNCTION; CYTOKINES; ISCHEMIA; MODELS; DAMAGE